Manitou Canyon [compact disc, unabridged] : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2016)
In the extraordinary new Cork O'Connor thriller from New York Times best selling and Edgar Award winning author William Kent Krueger, the lives of hundreds of innocent people are at stake when Cork vanishes just days before his daughter's wedding.